BTBD19 promotes colorectal cancer progression and correlates with adverse clinical outcomes - Yang, Changjiang; Geng, Xuhua; Zhao, Zihan (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a leading cause of cancer-related mortality worldwide. The identification of novel prognostic biomarkers and therapeutic targets is crucial for improving clinical management and patient outcomes. Members of the BTBD (BTB/POZ domain-containing) protein family have been implicated in tumorigenesis, but the role of BTBD19 in CRC remains poorly understood.ObjectiveThis study aimed to investigate the expression pattern of BTBD19 in CRC, its association with clinicopathological features and prognosis, and its potential molecular mechanisms involving functional pathways and immune infiltration.MethodsBTBD19 expression was analyzed using public datasets (TCGA, GEO) and clinical tissue microarrays. Immunohistochemistry (IHC) was performed to validate protein expression. Survival analysis (OS, DSS, PFI) was conducted to assess prognostic significance. Functional enrichment analyses (GO/KEGG/GSEA) and immune infiltration analyses (ESTIMATE, ssGSEA, CIBERSORT) were used to explore underlying molecular mechanisms and immune-related associations.ResultsBTBD19 was significantly upregulated in CRC tissues at both mRNA and protein levels compared to normal tissues. High BTBD19 expression was associated with advanced pathologic stages and poor prognosis (OS, DSS, PFI; all p<0.05). Functional analyses revealed that BTBD19-associated genes were enriched in pathways related to extracellular matrix organization, focal adhesion, and epithelial-mesenchymal transition. Immune infiltration analysis showed positive correlations between BTBD19 expression and stromal/immune scores, M2 macrophage infiltration, and expression of immune checkpoints (CD274, PDCD1).ConclusionBTBD19 is upregulated in CRC and promotes tumor progression. It may serve as a potential prognostic biomarker for CRC, with implications for understanding CRC pathogenesis and immune microenvironment regulation.